Zastosowanie wybranych metod ilościowych do oceny jakości wykonywania zamówień publicznych - Jóźwiak, Agnieszka (The Application of Selected Quantitative Methods to Assess Competitive Tendering Execution Quality, 2006)
The problem of the competitive tendering execution quality decreasing caused by an excessive reduction of the offered price was investigated. The author proposes the application of quantitative methods to assess. Ex post quality concerning road building and to forecast competitive tendering execution quality assessment. Binomial logit model, Fisher's linear discriminant analysis with Bayesian classification algorithm and nonparametric discriminant method (CART algorithm) were applied to assess the quality. The best results were obtained by using classification tree. It was shown that Fisher's discriminant analysis and logit model can't be used to assess competitive tendering execution quality. That is because the majority of predictors has irregular classes distribution and because the dependence between exogenous variate and endogenous variate is nonlinear.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 187-201